Kolme vuotta hyökkäyssotaa: Miten Venäjän talous on muuttunut?; How have three years of war changed the Russian economy? - Iikka Korhonen; Sinikka Parviainen; Heli Simola; Laura Solanko (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
– Russia's war of aggression, which has brought wide destruction and loss to Ukraine, has also transformed the Russian economy in significant ways. The Russian government's role in the economy has grown, with an ever-increasing amount of economic resources allocated to the war effort. The government, abandoning long-standing conservative fiscal discipline, now regards public sector deficits as acceptable. The country has managed to cover its budget deficits by draining the country's financial reserves and increasing domestic borrowing. While the point at which Russia loses its ability to wage war remains remote, its economic troubles are likely to snowball in the longer run.
urn:nbn:fi-fe2025022513905
Keywords: 330; Russia; economy; sanctions; economic policy; Volkswirtschaft; Russland